Acesso à justiça e os caminhos à efetividade do direito ao desenvolvimento - Marziale, Leonardo Palucci (2018)
The present work seeks to establish an interconnection of the concepts of Access to Justice and the Right to Development, under a Human Rights approach. Thus, first, is necessary to analyze some of the main Theories to stablish a north towards the concept of Justice in globalized and multicultural society. Subsequently, the present study will analyze the different development models and the main foundations for the notion of development aimed for the Right to Development movement, whose foundation will also be approached next, comprehending, also, its nexus with the access to justice, seen as an essential element for the its implementation.